High performance yet ethically risky? A self‐regulation perspective on the double‐edged sword effects of the performance‐oriented human resource system. Issue 2 (11th October 2021) - Zhang, Guanglei; Wang, Huaying; Ma, Rong; Li, Mingze
Abstract: Performance‐oriented human resource system (HRS) brings both benefits and risks to organizations. Prior studies mainly reported the positive impact of performance orientated HRS on organizational and employee performance, ignoring its negative impact on employee behavior. Based on self‐regulation theory, this paper examines the double‐edged sword effects of performance‐oriented HRS on employee outcomes. Multiwave data from a total of 253 employees indicated that perceived performance‐oriented HRS can predict employees' concerns with performance. This system could improve their willingness for self‐development, but it may also reduce employees' moral awareness, which increases employees' unethical behavior. Employees' self‐control moderates the negative effects of performance‐oriented HRS; that is, when employees' self‐control is low, performance‐oriented HRS leads to a stronger influence on employees' unethical behaviors through moral awareness than when it is high. The results enhance our knowledge of the effects of performance‐oriented HRS on employees' attitudinal and behavioral outcomes and provide new insights for countering the negative effects of performance‐oriented HRS in organizational human resource practices.